The Effect of Board Characteristics as Corporate Governance Attribute on Firm Performance in Pakistan - Faiza Saleem (UW Journal of Management Sciences, 2022)
Purpose: Most of the prior studies followed board characteristics as corporate governance attribute, the study to follow on the basis of literature support to use board characteristics as one of the corporate governance attributes. The objective of this research study is to investigate the effect of the board of director's characteristics on firm performance of the Pakistani oil and gas firms listed on Pakistan Stock Exchange (PSX). Methodology/Design: Data was collected from the annual reports of oil and gas firms listed on (PSX). The study applies pooled OLS regression on all oil and gas firms listed on PSX for the period from 2008-2015. Return on assets (ROA) is used as a proxy for measuring firm performance which is the dependent variable. Whereas the independent variables used in the study are board size, board independence, CEO duality, board activity. Findings: The board size and board independence are found significant factors of firm’s performance in Pakistan. Whereas, CEO duality and board activity are insignificant in determining the performance of firms in Pakistani oil and gas firms. Implications: The outcomes and findings of the present study are significant for, regulators, legislators and investors, in order to determine which governance mechanism is important in improving firm performance in Pakistan.